The characteristic and size–frequency distribution of rocks at the Zhurong landing site, Mars - Sun, Xiukuo; Li, Shouding; Li, Juan; Wu, Yanfang; Zhang, Shuo; Zheng, Bo; Zhang, Zhaobin; Xu, Tao; Chen, Xinshuo; Diao, Yiming (Frontiers in Astronomy and Space Sciences, 2024)
The rock characteristic and size–frequency distribution (SFD) on Mars are important for understanding the geologic and geomorphic history of the surface, for evaluating the trafficability of roving, and for planning the potential infrastructure construction. Tianwen-1, China’s first autonomous Mars exploration mission, formed an excavated depression during touchdown, which has been the deepest depression on the Martian surface so far compared with others. According to the images captured using the Navigation and Terrain Cameras (NaTeCams) onboard the rover, Zhurong, the SFD of rocks is calculated and compared inside the excavated depression, within and out of the blast zone. For the first time, the rock size distribution inside the excavated depression is obtained, exposing the geological features of the shallow subsurface on Mars at a depth of tens of centimeters, which will surely be important for future drilling missions. It is found that the rock abundance in the depression is smaller than the original abundance on the surface, and the distribution of rocks in the blast zone on the surface is greatly influenced by the touchdown. In addition, based on the fractal dimension of rock sizes, the rocks (>10 mm) at the shallow subsurface of the Zhurong landing site may experience two different geological processes.